The Effect of Potassium Fertilizer and Super-flora Foliar Fertilizer on the Growth of Chili Peppers (Capsicum frutescens L.) - Muhammad Haekal Zaqladi; M. Abror (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to determine the effect of potassium fertilizer and Super-Flora foliar fertilizer on the growth of chili pepper plants (Capsicum frutescens L.). The study was conducted using a randomized block design (RBD) with two treatment factors, namely potassium fertilizer dosage (100 kg/ha, 150 kg/ha, and 200 kg/ha) and Super-Flora foliar fertilizer dosage (10 ml/l, 15 ml/l, and 20 ml/l). The parameters observed included plant height, number of leaves, and leaf area at various plant ages. The results showed that the application of 200 kg/ha of potassium fertilizer and 20 ml/l of Super-Flora foliar fertilizer produced the best growth with an increase in plant height, number of leaves, and leaf area compared to other doses. Although the 5% BNJ test results did not show significant differences in all parameters, the data trends indicated that the combination of high-dose potassium fertilizer and high-dose foliar fertilizer supported more optimal vegetative growth. In conclusion, the combination of potassium fertilizer and Super-Flora foliar fertilizer can be an effective fertilization strategy to enhance chili pepper growth, but the doses used must be adjusted to the plants' needs for greater efficiency.